A method for preparing ultra-high strength alloy steel by metal powder injection molding

By using a mixture of gas atomized pre-alloyed powder and binder in the powder injection molding process, combined with nitric acid catalyzed degreasing and a three-stage sintering process, the problem in the existing technology that the heat treatment of steel in the powder injection molding process is difficult to control is solved , achieving the preparation of alloy steel with high strength, density and good heat treatment adjustability.

CN116174718BActive Publication Date: 2025-01-24SHENZHEN KADAM TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211106380.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-11
Publication Date
2025-01-24
Estimated Expiration
2042-09-11

AI Technical Summary

Technical Problem

The existing medium and low carbon steels are difficult to effectively control the heat treatment process in powder injection molding processes, resulting in hard and soft surfaces, high cost and low yield, which cannot meet the needs of lightweight, heavy-duty small precision components.

Method used

The gas atomized pre -alloy powder is mixed with the adhesive, and after heating and densely refining through high -scissors, the injection machine is injected into the mold in the mold. Then, the nitric acid catalytic dehydration furnace is subtracted, and the bonding agent is discharged with a three -stage sintering process and the oxide is restored.

Benefits of technology

The high intensity, density and good thermal treatment of alloy steel are realized, reducing the complexity and cost of thermal treatment, and the improvement of good products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116174718B_ABST
    Figure CN116174718B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of powder metallurgy materials, and more specifically, particularly relates to a method for preparing ultra-high-strength alloy steel by metal powder injection molding. The method can comprehensively improve the overall mechanical properties of the material, and elements such as Mn, Mo, Ni, and Cu can all improve the hardenability of the alloy steel, which is conducive to the use of a milder cooling medium during heat treatment and to enable the workpiece to obtain uniform and good mechanical properties, thereby reducing the complexity of heat treatment of the alloy steel. At the same time, a three-stage sintering process is specially designed, wherein the first stage at a lower temperature is mainly used to further discharge the binder, and the second stage at an intermediate temperature is mainly used to reduce the oxides of copper, nickel, molybdenum, etc. while ensuring that the carbon element is not lost, so that the powder is completely exposed to a fresh surface to facilitate subsequent sintering, and the temperature is slightly higher than the melting point of copper, which is conducive to the initial formation of a liquid phase to fill the pores and improve the overall density, and finally the temperature is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of powder metallurgy materials, and more specifically, particularly relates to a method for preparing ultra-high strength alloy steel by metal powder injection molding. Background Art

[0002] Metal powder injection molding is a near-net-shape forming technology that combines powder metallurgy with injection molding. It has the characteristics of wide material applicability, high raw material utilization, good dimensional accuracy, and excellent performance. In particular, it is more efficient and cost-effective than machining in the direct preparation of small and complex parts. In recent years, the ever-evolving high-end equipment has an increasing demand for lightweight and heavy-duty small precision parts (such as gears, etc.). In addition to using low-density high-strength aluminum, magnesium and other alloys, the development of alloy steels with higher strength suitable for metal powder injection molding production is also a very effective solution. However, in actual production, various existing medium and low carbon steels need to be improved through heat treatment processes such as carburizing and surface induction quenching to meet the service performance requirements, so that the parts are "hard on the surface and soft on the inside" to have better comprehensive properties such as wear resistance and fatigue resistance. Since these parts are relatively small in size and complex in shape, it is often difficult to effectively control the range of affected parts and ensure uniformity during the processing, resulting in high heat treatment costs and low yields. Therefore, there is an urgent need to develop a new type of high-strength alloy steel suitable for powder injection molding process and corresponding production parameters to meet the potential needs of related fields. Therefore, the present invention proposes a preparation method of ultra-high-strength alloy steel for metal powder injection molding. Summary of the invention

[0003] In view of the deficiencies in the prior art, the present invention provides a method for preparing ultra-high strength alloy steel by metal powder injection molding to solve the problems raised in the above background technology.

[0004] To achieve the above objectives, the present invention is implemented by the following technical scheme: A method for preparing ultra-high strength alloy steel by metal powder injection molding, comprising the following steps:

[0005] S1: Use gas atomized pre-alloyed powder mixture as raw material;

[0006] S2: Mix the pre-alloyed powder and the binder, heat and knead them in a mixing and granulating machine, and then extrude, cut and granulate them to obtain uniform particles;

[0007] S3: using an injection molding machine to inject the processed feed material into a mold to obtain a green body;

[0008] S4: using a nitric acid catalytic degreasing furnace to catalytically degrease the green embryo;

[0009] S5: After degreasing, the temperature is raised in three stages and then cooled down;

[0010] S6: The sintered part is heated and then water quenched, and then heated again and air-cooled or water-quenched to obtain alloy steel.

[0011] Preferably, the particle size of the gas atomized pre-alloyed powder in S1 is 1-25 μm, and the atomized pre-alloyed powder includes iron powder, iron-copper or copper-nickel powder, chromium-iron nitride powder, iron-manganese powder, nickel powder and molybdenum powder.

[0012] Preferably, the volume ratio of the pre-alloyed powder to the binder in S2 is 1:1-3:1, the granulator is a high shear mixing granulator, the heating temperature in the mixing granulator is 180°C, the mixing time is 1.5 hours, and the specification of the particles is: Φ2.5mm×3.2mm.

[0013] Preferably, in S3, the barrel temperature is 175-185°C, the nozzle temperature is 190-200°C, and the mold temperature is 90-120°C.

[0014] Preferably, the conditions of the nitric acid catalytic degreasing furnace in S4 are: temperature of 95-120°C, time of 5 hours, atmosphere of 99.999% purity nitrogen, and thermal degreasing using a two-stage heating process: heating from room temperature to 350°C at 3-5°C / min, keeping warm for 30-50min, and then heating from 350°C to 600°C at 2.5-3°C / min, keeping warm for 120min, completing thermal degreasing, and the atmosphere is 99.999% purity nitrogen.

[0015] Preferably, the specific steps of S5 are: after degreasing is completed, the temperature is increased to 950°C at 3-5°C / min, and kept warm for 0.5-1h, the atmosphere is argon with a purity of 99.999%, the temperature is increased from 950°C to 1080-1150°C at 2.5-3°C / min, and kept warm for 1-2h, the atmosphere is a mixture of argon with a purity of 99.999% and hydrogen with a volume ratio of 8:2-9:1, the temperature is increased to 1250-1280°C at 2.5-3°C / min, and kept warm for 1-3h, the atmosphere is argon with a purity of 99.999%, the temperature is reduced from 1280°C to 60°C at 3-100°C / min and then taken out, and the atmosphere is argon with a purity of 99.999%.

[0016] Preferably, the specific steps of S6 are: placing the sintered part in a high-temperature furnace with an atmosphere of argon or nitrogen with a purity of 99.999% and a temperature of 900-1050°C, keeping it warm for 0-30 minutes, and then quenching it with water; then placing the test piece in a high-temperature furnace with an atmosphere of argon or nitrogen with a purity of 99.999% and a temperature of 500-650°C, keeping it warm for 0-5 hours, and then air cooling or water quenching to obtain alloy steel.

[0017] The present invention provides a method for preparing ultra-high strength alloy steel by metal powder injection molding, which has the following beneficial effects:

[0018] The invention introduces three elements with strengthening effects into the alloy composition at the same time through the systematic alloy composition and powder injection molding and post-processing process design, namely, a medium-content C element that can improve the hardenability, a Cu element that can precipitate strengthening, and a N element that strongly strengthens the gap, so as to comprehensively improve the overall mechanical properties of the material, and elements such as Mn, Mo, Ni, and Cu can all improve the hardenability of the alloy steel, which is conducive to using a milder cooling medium during heat treatment and enabling the workpiece to obtain uniform and good mechanical properties, thereby reducing the complexity of heat treatment of the alloy steel. Meanwhile, a three-stage sintering process is specially designed, wherein the first stage has a lower temperature mainly for further discharging the binder, and the second stage has an intermediate temperature mainly for reducing the oxides of copper, nickel, molybdenum, etc. while ensuring that the carbon element is not lost, so that the powder is completely exposed to a fresh surface for subsequent sintering, and the temperature is slightly higher than the melting point of copper, which is conducive to the initial formation of a liquid phase to fill the pores and improve the overall density, and finally the temperature is increased, and the alloy is fully sintered to densify, so that the prepared material has high density, high strength, good heat treatment adjustability, simple process, and high yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a schematic diagram of a sintered part of the present invention;

[0020] Figure 2 This is the morphology of the middle part of the sintered part after grinding and polishing, and the metallographic structure after further corrosion. DETAILED DESCRIPTION

[0021] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0022] See also Figure 1 to Figure 2 The present invention provides a technical solution: a method for preparing ultra-high strength alloy steel by metal powder injection molding, which specifically comprises the following steps:

[0023] Step 1, selecting gas atomized pre-alloyed powder with a particle size of 1-25 μm or using hydroxy iron powder, iron copper or copper nickel powder (introducing copper element), chromium nitride iron powder (introducing nitrogen element), iron manganese powder (introducing manganese element), nickel powder and molybdenum powder mixture of the same particle size as raw materials, and designing the composition C: 0.5-0.7wt.%, Ni: 1.7-2.0wt.%, Mo: 0.5-0.7wt.%, Mn: 0.2-0.3wt.%, Cu: 0.1-1.3wt.%, N: 0.1-0.3wt.%, and the balance is Fe;

[0024] Step 2, the pre-alloyed powder and the binder are mixed in a volume ratio of 1:1-3:1, and then heated to 180°C in a high shear mixing granulator, kneaded for 1.5 hours, extruded, granulated, and granulated to obtain uniform particles of Φ2.5mm×3.2mm;

[0025] Step 3, using an injection molding machine to inject the treated feed into a mold to obtain a green body, wherein the barrel temperature is 175-185°C, the nozzle temperature is 190-200°C, and the mold temperature is 90-120°C;

[0026] Step 4, using a nitric acid catalytic degreasing furnace to catalytically degrease the green embryo at a temperature of 95-120°C for 5 hours, the atmosphere is 99.999% pure nitrogen, and then a two-stage heating process is used for thermal degreasing: heating from room temperature to 350°C at 3-5°C / min, keeping warm for 30-50min, and then heating from 350°C to 600°C at 2.5-3°C / min, keeping warm for 120min, completing thermal degreasing, the atmosphere is 99.999% pure nitrogen;

[0027] Step 5, after degreasing is completed, the temperature is increased to 950°C at 3-5°C / min, and the temperature is kept for 0.5-1h. The atmosphere is argon with a purity of 99.999%. The temperature is increased from 950°C to 1080-1150°C at 2.5-3°C / min, and the temperature is kept for 1-2h. The atmosphere is a mixture of argon with a purity of 99.999% and hydrogen (volume ratio 8:2-9:1). The temperature is increased to 1250-1280°C at 2.5-3°C / min, and the temperature is kept for 1-3h. The atmosphere is argon with a purity of 99.999%. The temperature is reduced from 1280°C to 60°C at 3-100°C / min and then taken out. The atmosphere is argon with a purity of 99.999%;

[0028] Step 6: Place the sintered part in a high-temperature furnace with an atmosphere of 99.999% argon or nitrogen and a temperature of 900-1050°C, keep it warm for 0-30 minutes, and then water quench it. Then, place the test piece in a high-temperature furnace with an atmosphere of 99.999% argon or nitrogen and a temperature of 500-650°C, keep it warm for 0-5 hours, and then air cool or water quench it to obtain an alloy steel with a good combination of strength and toughness.

[0029] Example 1

[0030] (1) A gas atomized pre-alloyed powder with a particle size of 1 μm is selected, wherein C, 0.5 wt. %; Ni, 1.7 wt. %; Mo, 0.5 wt. %; Mn, 0.2 wt. %; Cu, 0.1 wt. %; N, 0.1 wt. %; the balance is Fe;

[0031] (2) mixing the pre-alloyed powder and the binder in a volume ratio of 1:1, heating the mixture to 180°C in a high shear mixer and granulating the mixture for 1.5 hours, extruding, cutting and granulating the mixture to obtain a feed material of Φ2.5 mm×3.2 mm;

[0032] (3) using an injection molding machine to inject the treated feed material into a mold to obtain a green body, wherein the barrel temperature is 175° C., the nozzle temperature is 190° C., and the mold temperature is 90° C.;

[0033] (4) using a nitric acid catalytic degreasing furnace to catalytically degrease the green embryo at a temperature of 95°C for 5 hours in an atmosphere of 99.999% pure nitrogen, and then using a two-stage heating process for thermal degreasing: heating from room temperature to 350°C at 3°C / min, keeping the temperature for 30 minutes, and then heating from 350°C to 600°C at 2.5°C / min, keeping the temperature for 120 minutes, to complete the thermal degreasing, in an atmosphere of 99.999% pure nitrogen;

[0034] (5) After degreasing, the temperature was raised to 950°C at 3°C / min, kept at this temperature for 0.5h, and the atmosphere was argon gas with a purity of 99.999%. The temperature was raised to 1080°C at 2.5°C / min, kept at this temperature for 1h, and the atmosphere was a mixture of argon gas with a purity of 99.999% and hydrogen gas (volume ratio 8:2). The temperature was raised to 1250°C at 2.5°C / min, kept at this temperature for 1h, and the atmosphere was argon gas with a purity of 99.999%. The temperature was lowered from 1280°C to 60°C at 3°C / min, and then taken out, and the atmosphere was argon gas with a purity of 99.999%.

[0035] Example 2

[0036] (1) Selecting a gas atomized pre-alloyed powder with a particle size of 25 μm, the composition of which is C: 0.7 wt.%, Ni: 2.0 wt.%, Mo: 0.7 wt.%, Mn: 0.3 wt.%, Cu: 1.3 wt.%, N: 0.3 wt.%, and the balance is Fe;

[0037] (2) pre-alloyed powder and binder were mixed in a volume ratio of 3:1, and then heated to 180°C in a high shear mixer granulator for 1.5 hours, followed by extrusion, pelletization, and granulation to obtain a feed material of Φ2.5 mm×3.2 mm;

[0038] (3) using an injection molding machine to inject the treated feed material into a mold to obtain a green body, wherein the barrel temperature is 185° C., the nozzle temperature is 200° C., and the mold temperature is 120° C.;

[0039] (4) using a nitric acid catalytic degreasing furnace to catalytically degrease the green embryos at a temperature of 120° C. for 5 hours in an atmosphere of 99.999% pure nitrogen, and then using a two-stage heating process for thermal degreasing: heating from room temperature to 350° C. at 5° C. / min, keeping the temperature for 50 min, and then heating from 350° C. to 600° C. at 3° C. / min, keeping the temperature for 120 min, to complete the thermal degreasing, in an atmosphere of 99.999% pure nitrogen;

[0040] (5) After degreasing, the temperature was raised to 950°C at 5°C / min and kept for 1 hour. The atmosphere was argon with a purity of 99.999%. The temperature was raised from 950°C to 1150°C at 3°C / min and kept for 2 hours. The atmosphere was a mixture of argon with a purity of 99.999% and hydrogen (volume ratio 9:1). The temperature was raised to 1280°C at 3°C / min and kept for 3 hours. The atmosphere was argon with a purity of 99.999%. The temperature was lowered from 1280°C to 60°C at 100°C / min and then taken out. The atmosphere was argon with a purity of 99.999%.

[0041] (6) The sintered part was placed in a high-temperature furnace with an atmosphere of 99.999% argon and a temperature of 1050°C for 30 minutes and then water quenched. Subsequently, the test piece was placed in a high-temperature furnace with an atmosphere of 99.999% nitrogen and a temperature of 650°C for 5 hours and then water quenched to obtain an alloy steel with a good combination of strength and toughness;

[0042] Example 3

[0043] (1) Selecting a gas atomized pre-alloyed powder with a particle size of 25 μm, the composition of which is C: 0.6 wt.%, Ni: 1.8 wt.%, Mo: 0.6 wt.%, Mn: 0.25 wt.%, Cu: 0.12 wt.%, N: 0.2 wt.%, and the balance is Fe;

[0044] (2) pre-alloyed powder and binder were mixed in a volume ratio of 2:1, and then heated to 180°C in a high shear mixer granulator, kneaded for 1.5 hours, extruded, pelletized, and granulated to obtain a feed material of Φ2.5 mm×3.2 mm;

[0045] (3) using an injection molding machine to inject the treated feed material into a mold to obtain a green body, wherein the barrel temperature is 180° C., the nozzle temperature is 195° C., and the mold temperature is 100° C.;

[0046] (4) using a nitric acid catalytic degreasing furnace to catalytically degrease the green embryo at a temperature of 110° C. for 5 hours in an atmosphere of 99.999% pure nitrogen, and then using a two-stage heating process for thermal degreasing: heating from room temperature to 350° C. at 4° C. / min, keeping the temperature for 40 min, and then heating from 350° C. to 600° C. at 2.7° C. / min, keeping the temperature for 120 min, to complete the thermal degreasing, in an atmosphere of 99.999% pure nitrogen;

[0047] (5) After degreasing, the temperature was raised to 950°C at 4°C / min, and kept warm for 0.7h. The atmosphere was argon with a purity of 99.999%. The temperature was raised from 950°C to 1100°C at 2.7°C / min, and kept warm for 1-2h. The atmosphere was a mixture of argon with a purity of 99.999% and hydrogen (volume ratio of 85:15). The temperature was raised to 1270°C at 2.7°C / min, and kept warm for 2h. The atmosphere was argon with a purity of 99.999%. The temperature was lowered from 1280°C to 60°C at 50°C / min, and then taken out. The atmosphere was argon with a purity of 99.999%.

[0048] (6) The sintered part is placed in a high-temperature furnace with an atmosphere of 99.999% argon and a temperature of 1000°C for 15 minutes and then water quenched. Subsequently, the test piece is placed in a high-temperature furnace with an atmosphere of 99.999% argon and a temperature of 600°C for 2.5 hours and then air-cooled to obtain an alloy steel with a good combination of strength and toughness;

[0049] Example 4

[0050] (1) Selecting a gas atomized pre-alloyed powder with a particle size of 20 μm, the composition of which is C: 0.65 wt.%, Ni: 1.8 wt.%, Mo: 0.65 wt.%, Mn: 0.22 wt.%, Cu: 0.66 wt.%, N: 0.22 wt.%, and the balance is Fe;

[0051] (2) pre-alloyed powder and binder were mixed in a volume ratio of 2.5:1, and then heated to 180°C in a high shear mixer granulator, kneaded for 1.5 hours, extruded, pelletized, and granulated to obtain a feed material of Φ2.5 mm×3.2 mm;

[0052] (3) using an injection molding machine to inject the treated feed material into a mold to obtain a green body, wherein the barrel temperature is 178° C., the nozzle temperature is 192° C., and the mold temperature is 99° C.;

[0053] (4) using a nitric acid catalytic degreasing furnace to catalytically degrease the green embryo at a temperature of 105°C for 5 hours in an atmosphere of 99.999% pure nitrogen, and then using a two-stage heating process for thermal degreasing: heating from room temperature to 350°C at 3.5°C / min, holding for 45 minutes, and then heating from 350°C to 600°C at 2.8°C / min, holding for 120 minutes, to complete the thermal degreasing, in an atmosphere of 99.999% pure nitrogen;

[0054] (5) After degreasing, the temperature was raised to 950°C at 4.5°C / min, and kept warm for 0.85h. The atmosphere was argon with a purity of 99.999%. The temperature was raised from 950°C to 1090°C at 2.65°C / min, and kept warm for 1.6h. The atmosphere was a mixture of argon with a purity of 99.999% and hydrogen (volume ratio of 88:12). The temperature was raised to 1260°C at 2.8°C / min, and kept warm for 1.5h. The atmosphere was argon with a purity of 99.999%. The temperature was lowered from 1280°C to 60°C at 20°C / min, and then taken out. The atmosphere was argon with a purity of 99.999%.

[0055] (6) The sintered part was placed in a high-temperature furnace with a nitrogen atmosphere of 99.999% purity and a temperature of 1000°C for 20 minutes and then water quenched. Subsequently, the test piece was placed in a high-temperature furnace with an argon atmosphere of 99.999% purity and a temperature of 550°C for 3.5 hours and then air-cooled to obtain an alloy steel with a good combination of strength and toughness;

[0056] Example 5

[0057] (1) A mixture of 1 μm hydroxy iron powder, iron copper, chromium iron nitride powder, iron manganese powder, nickel powder and molybdenum powder is used as a raw material to prepare a composition of C: 0.5wt.%, Ni: 1.7wt.%, Mo: 0.5wt.%, Mn: 0.2wt.%, Cu: 0.1wt.%, N: 0.1wt.%, and the balance is Fe;

[0058] (2) pre-alloyed powder and binder were mixed in a volume ratio of 1:1, and then heated to 180°C in a high shear mixer granulator, kneaded for 1.5 hours, and extruded and granulated to obtain a feed material of Φ2.5 mm×3.2 mm;

[0059] (3) using an injection molding machine to inject the treated feed material into a mold to obtain a green body, wherein the barrel temperature is 175° C., the nozzle temperature is 190° C., and the mold temperature is 90° C.;

[0060] (4) using a nitric acid catalytic degreasing furnace to catalytically degrease the green embryo at a temperature of 95°C for 5 hours in an atmosphere of 99.999% pure nitrogen, and then using a two-stage heating process for thermal degreasing: heating from room temperature to 350°C at 3°C / min, keeping the temperature for 30 minutes, and then heating from 350°C to 600°C at 2.5°C / min, keeping the temperature for 120 minutes, to complete the thermal degreasing, in an atmosphere of 99.999% pure nitrogen;

[0061] (5) After degreasing, the temperature was raised to 950°C at 3°C / min, kept at this temperature for 0.5h, the atmosphere was argon gas with a purity of 99.999%, the temperature was raised from 950°C to 1080°C at 2.5°C / min, kept at this temperature for 1h, the atmosphere was a mixture of argon gas with a purity of 99.999% and hydrogen gas (volume ratio 8:2), the temperature was raised to 1250°C at 2.5°C / min, kept at this temperature for 1h, the atmosphere was argon gas with a purity of 99.999%, the temperature was lowered from 1280°C to 60°C at 3°C / min, and then taken out, the atmosphere was argon gas with a purity of 99.999%;

[0062] Example 6

[0063] (1) A mixture of hydroxy iron powder, copper-nickel powder, chromium iron nitride powder, iron-manganese powder, nickel powder and molybdenum powder with a particle size of 25 μm is selected as the raw material, and the composition is C: 0.7 wt.%, Ni: 2.0 wt.%, Mo: 0.7 wt.%, Mn: 0.3 wt.%, Cu: 1.3 wt.%, N: 0.3 wt.%, and the balance is Fe;

[0064] (2) pre-alloyed powder and binder were mixed in a volume ratio of 3:1, and then heated to 180°C in a high shear mixer granulator for 1.5 hours, followed by extrusion, pelletization, and granulation to obtain a feed material of Φ2.5 mm×3.2 mm;

[0065] (3) using an injection molding machine to inject the treated feed material into a mold to obtain a green body, wherein the barrel temperature is 185° C., the nozzle temperature is 200° C., and the mold temperature is 120° C.;

[0066] (4) using a nitric acid catalytic degreasing furnace to catalytically degrease the green embryos at a temperature of 120° C. for 5 hours in an atmosphere of 99.999% pure nitrogen, and then using a two-stage heating process for thermal degreasing: heating from room temperature to 350° C. at 5° C. / min, keeping the temperature for 50 min, and then heating from 350° C. to 600° C. at 3° C. / min, keeping the temperature for 120 min, to complete the thermal degreasing, in an atmosphere of 99.999% pure nitrogen;

[0067] (5) After degreasing, the temperature was raised to 950°C at 5°C / min and kept for 1 hour. The atmosphere was argon with a purity of 99.999%. The temperature was raised from 950°C to 1150°C at 3°C / min and kept for 2 hours. The atmosphere was a mixture of argon with a purity of 99.999% and hydrogen (volume ratio 9:1). The temperature was raised to 1280°C at 3°C / min and kept for 3 hours. The atmosphere was argon with a purity of 99.999%. The temperature was lowered from 1280°C to 60°C at 100°C / min and then taken out. The atmosphere was argon with a purity of 99.999%.

[0068] (6) The sintered part is placed in a high-temperature furnace with an atmosphere of 99.999% nitrogen and a temperature of 1050°C for 30 minutes and then water quenched. The test piece is then placed in a high-temperature furnace with an atmosphere of 99.999% argon or nitrogen and a temperature of 650°C for 5 hours and then air-cooled to obtain an alloy steel with a good combination of strength and toughness;

[0069] Example 7

[0070] (1) A mixture of hydroxy iron powder, iron copper, chromium iron nitride powder, iron manganese powder, nickel powder and molybdenum powder with a particle size of 15 μm is selected as the raw material, and the composition is C: 0.6wt.%, Ni: 1.8wt.%, Mo: 0.6wt.%, Mn: 0.25wt.%, Cu: 0.7wt.%, N: 0.2wt.%, and the balance is Fe;

[0071] (2) pre-alloyed powder and binder were mixed in a volume ratio of 2:1, and then heated to 180°C in a high shear mixer granulator, kneaded for 1.5 hours, extruded, pelletized, and granulated to obtain a feed material of Φ2.5 mm×3.2 mm;

[0072] (3) using an injection molding machine to inject the treated feed material into a mold to obtain a green body, wherein the barrel temperature is 180° C., the nozzle temperature is 195° C., and the mold temperature is 100° C.;

[0073] (4) using a nitric acid catalytic degreasing furnace to catalytically degrease the green embryo at a temperature of 110° C. for 5 hours in an atmosphere of 99.999% pure nitrogen, and then using a two-stage heating process for thermal degreasing: heating from room temperature to 350° C. at 4° C. / min, keeping the temperature for 40 min, and then heating from 350° C. to 600° C. at 2.6° C. / min, keeping the temperature for 120 min, to complete the thermal degreasing, in an atmosphere of 99.999% pure nitrogen;

[0074] (5) After degreasing, the temperature was raised to 950°C at 4°C / min, and kept for 0.6h. The atmosphere was argon with a purity of 99.999%. The temperature was raised from 950°C to 1110°C at 2.8°C / min, and kept for 1.5h. The atmosphere was a mixture of argon with a purity of 99.999% and hydrogen (volume ratio of 82:18). The temperature was raised to 1270°C at 2.8°C / min, and kept for 2h. The atmosphere was argon with a purity of 99.999%. The temperature was lowered from 1280°C to 60°C at 55°C / min, and then taken out. The atmosphere was argon with a purity of 99.999%.

[0075] (6) The sintered part is placed in a high-temperature furnace with an atmosphere of 99.999% argon and a temperature of 1000°C for 20 minutes and then water quenched. Subsequently, the test piece is placed in a high-temperature furnace with an atmosphere of 99.999% argon and a temperature of 500°C for 2.5 hours and then water quenched to obtain an alloy steel with a good combination of strength and toughness;

[0076] Example 8

[0077] (1) A mixture of hydroxy iron powder, iron copper, chromium iron nitride powder, iron manganese powder, nickel powder and molybdenum powder with a particle size of 20 μm is selected as the raw material, and the composition is C: 0.6wt.%, Ni: 1.8wt.%, Mo: 0.6wt.%, Mn: 0.25wt.%, Cu: 1.0wt.%, N: 0.2wt.%, and the balance is Fe;

[0078] (2) pre-alloyed powder and binder were mixed in a volume ratio of 2:1, and then heated to 180°C in a high shear mixer granulator, kneaded for 1.5 hours, extruded, pelletized, and granulated to obtain a feed material of Φ2.5 mm×3.2 mm;

[0079] (3) using an injection molding machine to inject the treated feed material into a mold to obtain a green body, wherein the barrel temperature is 180° C., the nozzle temperature is 195° C., and the mold temperature is 100° C.;

[0080] (4) using a nitric acid catalytic degreasing furnace to catalytically degrease the green embryo at a temperature of 110° C. for 5 hours in an atmosphere of 99.999% pure nitrogen, and then using a two-stage heating process for thermal degreasing: heating from room temperature to 350° C. at 4° C. / min, keeping the temperature for 40 min, and then heating from 350° C. to 600° C. at 2.6° C. / min, keeping the temperature for 120 min, to complete the thermal degreasing, in an atmosphere of 99.999% pure nitrogen;

[0081] (5) After degreasing, the temperature was raised to 950°C at 4°C / min, and kept for 0.6h. The atmosphere was argon with a purity of 99.999%. The temperature was raised from 950°C to 1110°C at 2.8°C / min, and kept for 1.5h. The atmosphere was a mixture of argon with a purity of 99.999% and hydrogen (volume ratio of 87:13). The temperature was raised to 1270°C at 2.8°C / min, and kept for 2h. The atmosphere was argon with a purity of 99.999%. The temperature was lowered from 1280°C to 60°C at 55°C / min, and then taken out. The atmosphere was argon with a purity of 99.999%.

[0082] (6) The sintered part is placed in a high-temperature furnace with an atmosphere of 99.999% nitrogen and a temperature of 1020°C for 20 minutes and then water quenched. Subsequently, the test piece is placed in a high-temperature furnace with an atmosphere of 99.999% nitrogen and a temperature of 550°C for 2.5 hours and then water quenched to obtain an alloy steel with a good combination of strength and toughness;

[0083] Example 9

[0084] (1) A mixture of hydroxy iron powder, iron copper, chromium iron nitride powder, iron manganese powder, nickel powder and molybdenum powder with a particle size of 15 μm is selected as the raw material, and the composition is C: 0.6wt.%, Ni: 1.8wt.%, Mo: 0.6wt.%, Mn: 0.25wt.%, Cu: 0.7wt.%, and the balance is Fe;

[0085] (2) pre-alloyed powder and binder were mixed in a volume ratio of 2:1, and then heated to 180°C in a high shear mixer granulator, kneaded for 1.5 hours, extruded, pelletized, and granulated to obtain a feed material of Φ2.5 mm×3.2 mm;

[0086] (3) using an injection molding machine to inject the treated feed material into a mold to obtain a green body, wherein the barrel temperature is 180° C., the nozzle temperature is 195° C., and the mold temperature is 100° C.;

[0087] (4) using a nitric acid catalytic degreasing furnace to catalytically degrease the green embryo at a temperature of 110° C. for 5 hours in an atmosphere of 99.999% pure nitrogen, and then using a two-stage heating process for thermal degreasing: heating from room temperature to 350° C. at 4° C. / min, keeping the temperature for 40 min, and then heating from 350° C. to 600° C. at 2.6° C. / min, keeping the temperature for 120 min, to complete the thermal degreasing, in an atmosphere of 99.999% pure nitrogen;

[0088] (5) After degreasing, the temperature was raised to 950°C at 4°C / min and kept for 0.6h. The atmosphere was argon with a purity of 99.999%. The temperature was raised from 950°C to 1110°C at 2.8°C / min and kept for 1.5h. The atmosphere was a mixture of argon with a purity of 99.999% and hydrogen (volume ratio of 82:18). The temperature was raised to 1270°C at 2.8°C / min and kept for 2h. The atmosphere was argon with a purity of 99.999%. The temperature was lowered from 1280°C to 60°C at 4°C / min and then taken out. The atmosphere was argon with a purity of 99.999%. The sintered parts were as shown in FIG. Figure 1 As shown, Figure 2 Figure a shows the morphology of the middle part of the sintered part after grinding and polishing, and the structure b after further corrosion.

[0089] It should be noted that: this method introduces three elements with strengthening effects into the alloy composition at the same time through the systematic alloy composition and powder injection molding and post-processing process design, namely, medium-content C element that can improve hardenability, Cu element that can precipitate strengthening and N element that strongly strengthens the gap, which comprehensively improves the overall mechanical properties of the material, and Mn, Mo, Ni, Cu and other elements can improve the hardenability of alloy steel, which is conducive to the use of milder cooling medium during heat treatment and the workpiece obtains uniform and good mechanical properties, and high comprehensive performance can be achieved without or with only simple heat treatment. In addition, the powder used in metal powder injection molding is fine and highly active, and its surface is easily oxidized and affects the sintering densification process, which has a serious adverse effect on the performance of the final product. To address this problem, this application has specially designed a three-stage sintering process, in which the first stage at a lower temperature is mainly used to further expel the binder, and the second stage at an intermediate temperature is mainly used to reduce the oxides of copper, nickel, molybdenum, etc. while ensuring that the carbon element is not lost, so that the powder can completely expose the fresh surface to facilitate subsequent sintering. This temperature is slightly higher than the melting point of copper, which is conducive to the initial formation of a liquid phase to fill the pores and improve the overall density. Finally, the temperature is increased to fully sinter and densify the alloy.

[0090] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing ultra-high strength alloy steel by metal powder injection molding, characterized in that it comprises the following steps: S1: Use gas atomized pre-alloyed powder mixture as raw material; S2: Mix the pre-alloyed powder and the binder, heat and knead them in a mixing and granulating machine, and then extrude, cut and granulate them to obtain uniform particles; S3: using an injection molding machine to inject the processed feed material into a mold to obtain a green body; S4: using a nitric acid catalytic degreasing furnace to catalytically degrease the green embryo; S5: After degreasing, the temperature is raised in three stages and then cooled down; S6: heating the sintered part and then quenching it with water, and then heating it again and air cooling or water quenching it to obtain alloy steel; the particle size of the gas atomized pre-alloyed powder in S1 is: 1-25 μm, and the atomized pre-alloyed powder includes: Iron powder, iron copper or copper nickel powder, chromium iron nitride powder, iron manganese powder, nickel powder and molybdenum powder, the volume ratio of pre-alloyed powder to binder in S2 is 1:1-3:1, the granulator is a high shear mixing granulator, the heating temperature in the mixing granulator is 180°C, the mixing time is 1.5 hours, the specification of the particles is: Φ2.5mm×3.2mm, the barrel temperature in S3 is 175-185°C, the nozzle temperature is 190-200°C, the mold temperature is 90-120°C, S4 The conditions of the nitric acid catalytic degreasing furnace are: temperature 95-120℃, time 5 hours, atmosphere 99.999% pure nitrogen, two-stage heating process for thermal degreasing: 3-5℃ / min from room temperature to 350℃, keep warm for 30-50min, then 2.5-3℃ / min from 350℃ to 600℃, keep warm for 120min, complete thermal degreasing, atmosphere 99.999% pure nitrogen, the specific steps of S5 are: after degreasing is completed, heat at 3-5℃ / min to 950℃, keep warm for 0.5-1h, the atmosphere is 99.999% pure argon, heat up from 950℃ to 1080-1150℃ at 2.5-3℃ / min, keep warm for 1-2h, the atmosphere is a mixture of 99.999% pure argon and hydrogen, volume ratio 8:2-9:1, heat up to 1250-1280℃ at 2.5-3℃ / min, keep warm for 1-3h, the atmosphere is 99.999% pure argon, heat up at 3-1 The temperature is decreased from 1280°C to 60°C at a rate of 00°C / min, and then taken out, the atmosphere is argon with a purity of 99.999%. The specific steps of S6 are: placing the sintered part in a high-temperature furnace with an atmosphere of argon or nitrogen with a purity of 99.999% and a temperature of 900-1050°C, keeping it warm for 0-30min, and then quenching it with water; then placing the test piece in a high-temperature furnace with an atmosphere of argon or nitrogen with a purity of 99.999% and a temperature of 500-650°C, keeping it warm for 0-5h, and then air cooling or water quenching to obtain the alloy steel.

Citation Information

Patent Citations

  • High-strength wear-resistant high-temperature-resistant automobile blade and preparation method thereof

    CN112676566A

  • HIGH-STRENGTH NON-MAGNETIC STEEL

    RU2010116891A